Occurence of GDP-L-fucose: beta-N-acetylglucosamine (Fuc to asn-linked GlcNAc) alpha 1,6-fucosyltransferases in porcine, sheep, bovine, rabbit and chicken tissues - Struppe, E; Staudacher, E (Biochimica et biophysica acta, 2000)
Transgenic animals are a promising source of pharmaceutically-relevant proteins or as a source of organs for xenotransplantation. Beside other posttranslational modifications, glycosylation has been shown to be a critical parameter for the correct function of several glycoproteins. To analyse the contribution of alpha 1,6-fucosylation to N-glycan variability, we partly purified alpha 1,6-fucosyltransferase (alpha 1,6-Fuc-T) activities from various tissues (brain, lung, heart, liver) of agriculturally-relevant animals (porcine, sheep, bovine, rabbit, chicken) and compared some of their biochemical properties. All tissues displayed alpha1,6-Fuc-T activity, although at different levels. No differences were observed in their stability against chemicals, temperature or time, whereas the activities were distinguishable by their pH-optima and their cation preferences. Similarities were found for tissues between species. Lung and heart enzymes showed a narrow pH-optimum around pH 6.0 and an enhanced activity in the presence of divalent cations. alpha 1,6-Fuc-T activities in brain and liver were characterised by a broad pH-optimum from 5.5 to 8.0. Some activities of these tissues were decreased by the addition of EDTA, while others did not show any influence of EDTA or divalent cations. From the significant differences of the alpha 1,6-Fuc-T activities in the tissues, it is possible to hypothesise the presence of more than one single alpha 1, 6-Fuc-T in mammalian tissues.